2011
DOI: 10.1016/j.infbeh.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Potential underlying mechanisms for greater weight gain in massaged preterm infants

Abstract: In this paper, potential underlying mechanisms for massage therapy effects on preterm infant weight gain are reviewed. Path analyses are presented suggesting that: 1) increased vagal activity was associated with 2) increased gastric motility, which, in turn, was related to 3) greater weight gain; and 4) increased IGF-1 was related to greater weight gain. The change in vagal activity during the massage explained 49% of the variance in the change in gastric activity. And, the change in vagal activity during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…These findings suggested two potential pathways by which massage can increase weight gain: 1) insulin release via the celiac branch of the vagus; and 2) increased gastric activity via the gastric branch of the vagus. 7 …”
Section: Preterm Infantsmentioning
confidence: 99%
“…These findings suggested two potential pathways by which massage can increase weight gain: 1) insulin release via the celiac branch of the vagus; and 2) increased gastric activity via the gastric branch of the vagus. 7 …”
Section: Preterm Infantsmentioning
confidence: 99%
“…However, more recent evidence indicates that MT in infants or preterm infants with low birth weight increases weight gain, 12–14 shortens hospital stay, 12 improves sleep quality, 15 reduces stress behaviours 16 and improves neurodevelopmental outcomes as the child ages 17 . Although the mechanism of action for paediatric massage is unknown, a recent paper by Field, Diego and Hernandez‐Reif postulates that the greater weight gain seen in massaged infants could be associated with increased vagal activity, increased gastric motility (as a result of increased vagal activity) and increased levels of insulin and insulin‐like growth factor‐1 (IGF‐1) 18 …”
Section: Overview Of the Evidence For Massage Therapymentioning
confidence: 99%
“…Newborns of prenatally depressed mother showed less responsiveness to stimuli in several studies (Field, 2011). Weinberg et al (2008) evaluated the effects of maternal depression and panic disorder, and found that infants belonging to these two groups showed similar “still face behavior” as infants from non-clinical samples.…”
Section: Introductionmentioning
confidence: 97%